The Emergence of the “I” Reflections on the Use of Qualitative Research Methods in a Master´s Program in Educational Management and Leadership at the VNU University of Education - Narrowe, Judith (VNU Journal of Science: Education Research, 2014)
Abstract: Qualitative interactive research methods by definition necessitate the conscious and active involvement and participation on the part of both researcher and researched. Using as a point of departure a masters course in educational management and leadership in Hanoi, Vietnam, conducted jointly by Högskolan Dalarna in Sweden and the staff of the University of Education in Hanoi, this article explores several aspects of the qualitative research process as it was  conducted by eight Vietnamese educational managers in their masters´ theses. The article focuses in particular on how the qualitative methods contributed to the construction of the informal backstage where an interpersonal dynamic and a reflective dialogue could take place. In this arena, we can view the emergence of the personal “I” of the researcher.  The paper concludes with some thoughts on  activities of the supervisor. Keywords: Backstage, ethnography, experience, reflective dialogue, qualitative methods.